(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The building of a new international cultural order is an important part of the construction of a new, fairer, more equitable and reasonable international order. However, the new international cultural order is still in its co nstruction stage, and in this process, faced with the fierce competition of international forces, the stirring of different political trends and the profound adjustment of unequal interests, the road to building a new international cultural order is long a nd winding, the number of troubling factors is increasing, and the difficulty is growing. In this regard, countries around the world need to make efforts to explore a model of national interaction based on mutual tolerance, mutual respect and common develo pment, so as to avoid vicious competition among major powers; strengthen theoretical research on world politics, so as to lay the theoretical foundation and value basis for the construction of a new paradigm of international cultural order; and promote the rise of emerging market countries and developing countries as a group, so as to build a solid power base for the construction of a new international cultural order.